Clinical and Anatomical Changes induced by Sciatic Nerve Section of Weaning Age Rabbits - Ban Ismael Sedeeq; Ayad Hammeed Ibrahim; Abul Kareem Salem Mahood (Tikrit Journal of Pure Science)
The aim of the study was to explore the clinical and anatomical changes occured after Sciatic nerve section in the weaning age in rabbits. Twenty-five rabbits were used in this study ranging from 1-2.5 months. Divided into five subgroups according to the number of survival days (W7) (W14) (W30) (W60) (W90). Surgery was performed under general anesthesia. The nerve was sectioned using a small surgical scissor. Clinicalay few days later, the sign of right hind paws paralysis was observed clearly. The results revealed of a gap formation between the two nerve stumps [proximal and distal], and the gap increases on the day fourteenth. During the following two weeks, ulcers began to appear in the skin at the dorsal side of the ankle joint, and there was also an enlarged popliteal lymph node. Within 30-60 days another area was invaded by ulcer with or without bone exposure, the anterior part of the posterior side of the hind limb. After 90 days, there was severe ulceration and bone exposure with enlarged lymph nodes and the ulceration extended to the ventral side of the hindlimb. Results showed a gradual worsening of the condition and without improvement in peripheral nerves.